(3cja JUHM fGLMG aj GdMjGI? (B:s 100 (3OQS ddfLGM ef (B((3hjd SejK(B) /s - (3Qhf(B, (3Jhfjs ((3GdchjJ(B:s (3OGQ TZa(B,s, 2016)
(3cd EfSGf jQZH Cf jchf fGLMkG; dJchf fGLMkG aj gPg GdMjGI, adGHO Cf jchf dOjc EJLGg EjLGHj JLGg GdMjGI(B. (3agPG GdGJLGg GdEjLGHj fMh GdMjGI gh GdTjF GdhMjO GdPj jSGYO GdEfSGf Ydi JMbjb GQJaGYGJ cHjQI aj GdMjGI(B. (3aEf CcKQ GdCTNGU fLGMkG aj GdYGde OGFekG eG EQJaYhG ahb eTGcdge hJahbhG Ydi efGaSjge(B. (3dJMbb CgOGa MjGJc Ydjc Cf JOQS JYGdje GdPjf CfLRhG fLGMGJge Yf cKH(B. (3JJYde GdOQhS GdeSJbGI efge hJYOjdgG dGSJNOGegG aj MjGJc GdNGUI JHYG ddehGba GdJj SJbGHdgG(B.s
Keywords: (3bUI fLGMs; (3hjd SejKs